How to Talk About Attitudes Toward the End of Life: A Qualitative Study. (August 2019) - Groebe, Bernadette; Rietz, Christian; Voltz, Raymond; Strupp, Julia
To individually plan end-of-life care, open communication about a person's preferences and attitudes toward the end of life can facilitate dignity and quality of life in patients and relatives. To improve communication, structured guiding tools might be used as door openers. However, most tools focus on care preferences and decisions without assessing the person's underlying attitudes in detail. This study aims to get insights into specific requirements and conditions for communication about the end of life in various end-of-life care settings. Four focus groups were conducted with volunteers and professionals from nursing and psychosocial care (16 females, 2 males) working in hospice and palliative care and long-term care settings in Germany. A semistructured interview guideline on experiences and aspects associated with end-of-life conversations was used. Interviews were audiotaped, transcribed verbatim, and analyzed by a content analytic approach. Having end-of-life discussions primarily depended on a pleasant atmosphere, trusting bonds between conversation partners, and professional attitudes of staff members. Nursing home staff felt obligated to initiate conversations, but some reported insecurities doing so. Starting "early, " including relatives, and having continuous discussions seemed beneficial for end-of-life conversations. Implementing conversations into existing care structures and using low-threshold impulses to start conversations were helpful. Individualized approaches should be preferred. Each staff member can be a partner in detailed conversations about end-of-life attitudes, but some felt unprepared doing so. Further skill training concerning end-of-life discussions is needed. Communication might be facilitated by open-format tools using low-threshold impulses when conditions of the care setting are considered.